Glass fiber reinforced nylon material with high alcoholysis resistance

Through the mixing and modification process of specific proportions and pretreated materials, high alcoholylated glass fiber reinforced nylon materials were prepared, which solved the problems of hydrolysis resistance, thermal stability and surface quality in the prior art, and improved the mechanical of the material Strength and fluidity have expanded the scope of application.

CN119307093APending Publication Date: 2025-01-14HANGZHOU ZETONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411647242.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

While improving hydrolysis resistance, existing glass fiber reinforced nylon materials are difficult to improve thermal stability, chemical properties and surface quality at the same time. The addition of glass fiber will lead to a decrease in fluidity and affect the injection molding process.

Method used

Use specific proportions of PA46, PA66, PA11, bio-based nylon, glass fiber, polyethylene and other materials for pretreatment and mixing, add mica, hollow glass microbeads and silane coupling agent, and pass the modification treatment and extrusion molding process. Prepare highly resistant alcoholylated fiber reinforced nylon material.

Benefits of technology

It significantly improves the mechanical strength, heat resistance, chemical corrosion resistance and surface quality of the material, reduces the difficulty of injection molding, expands the application range of products, and improves the stability and appearance quality of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a glass fiber reinforced nylon material with high alcoholysis resistance, and relates to the technical field of glass fiber reinforced nylon materials. Raw materials of the high-strength and high-toughness composite material comprise the following components in parts by weight: 30-43 parts of PA46, 20-25 parts of PA66, 15-7 parts of PA115, 3-5 parts of bio-based nylon, 20-45 parts of alkali-free glass fibers, 1-3 parts of polyethylene, 0.5-3 parts of an antioxidant, 0.2-3 parts of a heat stabilizer, 0.1-5 parts of a compatilizer, 1-5 parts of a flexibilizer, 0.2-0.5 part of a hydrolysis-resistant agent, 1-2 parts of an ultraviolet light absorber, 0.1-2 parts of a silane coupling agent, 0.1-0.5 part of a nucleating agent, 1-5 parts of hollow glass beads and 3-8 parts of mica. The glass fiber reinforced nylon material is prepared by mixing the raw materials according to the set proportion and sequence, the glass fiber reinforced fiber material with high alcoholysis resistance is finally obtained, a small amount of mica is added into the matrix raw materials, the insulativity and heat resistance of the prepared glass fiber reinforced nylon material are improved to a certain extent, and the service life of the glass fiber reinforced nylon material is prolonged. The range of products made of the material is expanded, the stability of the products is improved, and the products can resist corrosion of strong acid and strong alkali.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber reinforced nylon materials, in particular to a glass fiber reinforced nylon material with high alcoholysis resistance. Background Art

[0002] Reinforced nylon materials are composite materials that significantly improve performance by adding glass fibers, toughening agents, etc. to nylon. These materials are widely used in industrial fields that require high strength, high heat resistance and good dimensional stability, such as: for manufacturing engine peripheral components, body structural parts, and for producing various insulators and structural parts.

[0003] The defects of existing glass fiber reinforced nylon materials are:

[0004] 1. Patent document CN107298855B discloses a hydrolysis-resistant alcoholysis-reinforced nylon material and a preparation method thereof. It mainly considers how to improve the hydrolysis-resistant alcoholysis of the composite material while having excellent processing temperature resistance, but does not consider how to improve the chemical resistance and thermal stability of the glass fiber nylon material;

[0005] 2. Patent document CN107236296B discloses nylon glass fiber reinforced alcoholysis resistant material, which mainly considers how to make the composite material have excellent alcoholysis resistance and high impact resistance, but does not consider how to avoid the reduction of fluidity due to the addition of glass fiber, thereby affecting subsequent injection molding;

[0006] 3. Patent document CN111662546B discloses a high glass fiber reinforced nylon composite material and its preparation method and application. It mainly considers how to retain the inherent mechanical and thermal properties of glass fiber reinforced nylon materials while having excellent surface quality and weather resistance, but does not consider how to improve the surface quality of the product while improving the alcoholysis resistance of the material;

[0007] 4. Application document CN115710429A discloses a hydrolysis-resistant and alcoholysis-resistant reinforced nylon material and a preparation method thereof. It mainly considers how to avoid the high temperature and humidity environment that accelerates the hydrolysis of the nylon material, and does not consider improving the performance of each raw material through pretreatment, thereby improving the performance of the final product. Summary of the invention

[0008] The object of the present invention is to provide a glass fiber reinforced nylon material with high alcoholysis resistance to solve the problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical scheme: a high alcoholysis-resistant glass fiber reinforced nylon material, wherein the raw materials thereof include the following components by weight: 30-43 parts of PA46, 20-25 parts of PA66, 7 parts of PA115, 3-5 parts of bio-based nylon, 20-45 parts of alkali-free glass fiber, 1-3 parts of polyethylene, 0.5-3 parts of antioxidant, 0.2-3 parts of heat stabilizer, 0.1-5 parts of compatibilizer, 1-5 parts of toughening agent, 0.2-0.5 parts of hydrolysis-resistant agent, 1-2 parts of ultraviolet absorber, 0.1-2 parts of silane coupling agent, 0.1-0.5 parts of nucleating agent, 1-5 parts of hollow glass microspheres, and 3-8 parts of mica;

[0010] PA46, PA66, PA11, bio-based nylon, glass fiber, polyethylene, antioxidant, heat stabilizer, compatibilizer, toughening agent, hydrolysis resistance agent, UV absorber, silane coupling agent, nucleating agent, hollow glass microspheres and mica are mixed to prepare glass fiber reinforced nylon material, which has better alcoholysis resistance than conventional nylon material.

[0011] Preferably, the mica is one or more of muscovite, phlogopite, biotite, lepidolite, and sericite, and its particle size range is 1-200 μm.

[0012] Preferably, the glass fiber has a diameter of 5-7 μm and a length of 1-2 mm.

[0013] Preferably, the particle size of the hollow glass microspheres is in the range of 10-20 mm.

[0014] A glass fiber reinforced nylon material with high alcoholysis resistance, wherein the nucleating agent is one of an inorganic nucleating agent, an organic nucleating agent and a polymer nucleating agent.

[0015] Preferably, the preparation method of the highly alcoholysis-resistant glass fiber reinforced nylon material is as follows:

[0016] Step S1: raw material pretreatment: modifying the alkali-free glass fiber to obtain modified glass fiber, and drying, toughening modification and weathering modification of PA46, PA66, PA11 and bio-based nylon respectively;

[0017] Step S2: high-speed mixing: adding the modified glass fiber in step S1, the pretreated PA46, PA66, PA11 and bio-based nylon, polyethylene, heat stabilizer, compatibilizer, hydrolysis resistance agent, silane coupling agent, nucleating agent, hollow glass microspheres and mica to a high-speed stirring agent in sequence and mixing to obtain a composite material;

[0018] Step S3: extrusion molding: extruding the mixed composite material through a twin-screw extruder to obtain the final alcoholysis-resistant glass fiber reinforced nylon material;

[0019] Step S4: post-treatment: placing the alcoholysis-resistant glass fiber reinforced nylon material obtained in step S3 into hot water at a constant temperature of 80-90° C., keeping the temperature for 40-50 minutes, and performing drying treatment;

[0020] Step S5: Performance test: Perform a comprehensive quality test on the alcoholysis-resistant glass fiber reinforced nylon material treated in step S4.

[0021] Preferably, the step S1 further includes the following steps:

[0022] Step S11: Modifying glass fiber: firstly using a silane coupling agent to perform surface treatment on the glass fiber, and then using nanoparticles to modify the surface of the glass fiber;

[0023] Step S12: Drying treatment: First, PA46, PA66, PA11 and bio-based nylon are dried respectively, wherein the drying temperature is 90-100° C. and the drying time is 2 hours;

[0024] Step S13: toughening modification: then, toughening agents are added to the dried PA46, PA66, PA11 and bio-based nylon respectively, and mixed by a high-speed mixer, wherein the stirring speed of the high-speed mixer is 800-900 rpm, and the stirring time is 20-30 min;

[0025] Step S14: Weathering resistance modification: Then add the ultraviolet absorber to the materials stirred in step S13, continue stirring at a speed of 800-900 rpm for 20-30 minutes, and then add the antioxidant to the high-speed mixer and stir at a speed of 800-900 rpm for 20 minutes.

[0026] Preferably, the step S2 further includes the following steps:

[0027] Step S21: Preliminary mixing: first add PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer into a high-speed mixer, and stir at a speed of 900-1000 rpm for 30-45 minutes at room temperature to form a premix;

[0028] Step S22: high temperature mixing: then add silane coupling agent, nucleating agent, hollow glass microspheres and mica to the premix, and continue mixing for 10-20 minutes at a heating temperature of 320-350° C. to obtain a composite material.

[0029] Preferably, the step S3 further includes the following steps:

[0030] Step S31: extrusion granulation: the mixed composite material is added into a twin-screw extruder from a main feed port, and extrusion granulation is performed under the conditions of an extrusion temperature of 255-260° C. and a rotation speed of 850 rpm;

[0031] Step S32: Cooling and pelletizing: firstly cool the material extruded in step S31 with water, and then pelletize it with a special pelletizer to obtain the final alcoholysis-resistant glass fiber reinforced nylon material.

[0032] Preferably, the step S5 further includes the following steps:

[0033] Step S51: Physical property test: the prepared alcoholysis-resistant glass fiber reinforced nylon material is placed in a drying oven at 120°C for 5 hours, and then the dried material is injected into a sample by an injection molding machine, and the mold temperature is 70°C. Then, the tensile strength is tested according to the ISO527-2 method, the bending strength is tested according to the ISO178 method, and the heat deformation temperature is tested according to the national standard GB / T1634.1. At the same time, the material is visually evaluated for its apparent quality. The custom apparent quality score is 0-10, where 10 points means that the material surface is smooth and has no floating fibers, and 0 points means that 80% to 100% of the surface area of ​​the material has floating fibers;

[0034] Step S52: Environmental resistance test: A hydrolysis and alcoholysis resistance test was performed according to Volkswagen TL52682 standard. The sample was placed in a mixed solution at 100° C. and a volume ratio of ethylene glycol to aqueous solution of 1:1 for 7 days, and then its tensile strength and bending strength were tested and the apparent quality of the sample was observed.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The glass fiber reinforced nylon material of the present invention is prepared by mixing raw materials in a set ratio and order, and finally obtaining a glass fiber reinforced fiber material with high alcoholysis resistance. By adding a small amount of mica to the matrix raw material, the insulation and heat resistance of the prepared glass fiber reinforced nylon material are improved to a certain extent, the range of products that can be made from the material is expanded, and the stability of the products is improved, which helps the products resist corrosion from strong acids and strong alkalis.

[0037] 2. In the preparation process of the present invention, hollow glass microspheres with a particle size of 10-20 mm are added, which can improve the addition of glass fiber to a certain extent and reduce the fluidity of nylon. The hollow glass microspheres have the characteristics of light weight and high thermal insulation while having high fluidity, so as to optimize the fluidity of the material, thereby reducing the difficulty of injection molding of the material and improving the overall performance and quality of the product.

[0038] 3. The present invention can significantly improve the mechanical strength, heat resistance and chemical corrosion resistance of the material by adding a set amount of glass fiber to nylon. The glass fiber may be exposed on the surface of the product during the injection molding process, causing the surface of the product to become rough, and then surface defects such as floating and material flowers will appear. The addition of silane coupling agent can improve the problem of product surface roughness to a certain extent. By mixing PA46, PA66, PA11, bio-based nylon and glass fiber in a certain proportion, the surface quality is further improved, the occurrence of floating fibers is reduced, and the appearance quality of the product is improved.

[0039] 4. The present invention pre-treats PA46, PA66, PA11, bio-based nylon and glass fiber to improve the toughness and aging properties of PA46, PA66, PA11 and bio-based nylon materials, and improves the interfacial bonding strength of glass fiber, which is conducive to the subsequent mixing of glass fiber with PA46, PA66, PA11 and bio-based nylon, thereby improving the hydrolysis and alcoholysis resistance and physical properties of the final product. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention provides a high alcoholysis-resistant glass fiber reinforced nylon material, and the preparation method of the high alcoholysis-resistant glass fiber reinforced nylon material is as follows:

[0042] Step S1: Raw material pretreatment: firstly, the glass fiber is surface treated with a silane coupling agent, and then the surface of the glass fiber is modified with nanoparticles, and the glass fiber is modified and set aside, and then PA46, PA66, PA11 and bio-based nylon are dried at a temperature of 90-100°C for 2 hours, and then toughening agents are added to the dried PA46, PA66, PA11 and bio-based nylon, and mixed with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 800-900rpm, and the stirring time is 20-30min, and then an ultraviolet absorber is added, and the stirring is continued at a speed of 800-900rpm. Stir for 20-30 minutes, then add the antioxidant into the high-speed mixer and stir at a speed of 800-900rpm for 20 minutes, wherein the mass ratio of PA46, toughening agent, ultraviolet absorber and antioxidant is (30-43): (2-3): 0.7: (0.5-1), the mass ratio of PA66, toughening agent, ultraviolet absorber and antioxidant is (20-25): (1-2): 0.5: (0.3-0.7), the mass ratio of PA11, toughening agent, ultraviolet absorber and antioxidant is (5-7): 0.5: 0.2: 0.2, and the mass ratio of bio-based nylon, toughening agent, ultraviolet absorber and antioxidant is (3-5): (0.1-0.5): 0.1: 0.1;

[0043] Step S2: high-speed mixing: firstly, the PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistant agent and compatibilizer treated in step S1 are added into a high-speed mixer, and stirred at a speed of 900-1000 rpm for 30-45 min at room temperature to form a premix, and then a silane coupling agent, a nucleating agent, hollow glass microspheres and mica are added into the premix, and the premix is ​​mixed for 10-20 min at a heating temperature of 320-350° C. to obtain a composite material, wherein PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistant agent and compatibilizer are added into a high-speed mixer, and stirred at a speed of 900-1000 rpm for 30-45 min at room temperature to form a premix, and then a silane coupling agent, a nucleating agent, hollow glass microspheres and mica are added into the premix, and the premix is ​​mixed for 10-20 min at a heating temperature of 320-350° C. to obtain a composite material. The mass ratio of olefin, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microsphere and mica is (30-43): (20-25): (5-7): (3-5): (1-3): (20-45): (0.2-3): (0.2-0.5): (0.1-5): (0.1-2): (0.1-0.5): (1-5): (3-8), the particle size range of mica is 1-200 μm, the diameter of glass fiber is 5-7 μm, the length is 1-2 mm, and the particle size range of hollow glass microsphere is 10-20 mm;

[0044] Step S3: extrusion molding: the mixed composite material is added into a twin-screw extruder from a main feed port, and extrusion granulation is performed under the conditions of an extrusion temperature of 255-260° C. and a rotation speed of 850 rpm, and then the extruded material is cooled with water, and then pelletized with a dedicated pelletizer to obtain the final alcoholysis-resistant glass fiber reinforced nylon material;

[0045] Step S4: post-treatment: placing the alcoholysis-resistant glass fiber reinforced nylon material obtained in step S3 into hot water at a constant temperature of 80-90° C., keeping the temperature for 40-50 minutes, and performing drying treatment;

[0046] Step S5: Performance test: Perform a comprehensive quality test on the alcoholysis-resistant glass fiber reinforced nylon material treated in step S4.

[0047] Further, the values ​​in steps S1 and S2 are changed, and step S3-5 is performed to evaluate the physical properties and alcoholysis resistance of the prepared alcoholysis-resistant glass fiber reinforced nylon material.

[0048] Embodiment 1:

[0049] Step S1: raw material pretreatment: first use a silane coupling agent to perform surface treatment on the glass fiber, then use nanoparticles to modify the surface of the glass fiber, and then use the modified glass fiber for standby use, then dry PA46, PA66, PA11 and bio-based nylon at a temperature of 90°C for 2 hours, then add toughening agents to the dried PA46, PA66, PA11 and bio-based nylon, and mix them with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 850rpm, and the stirring time is 25min, and then add ultraviolet absorbers, The mixture was stirred at 850 rpm for 20 min, and then the antioxidant was added into the high-speed mixer and stirred at 850 rpm for 20 min, wherein the mass ratio of PA46, toughening agent, UV absorber and antioxidant was 40:2:0.7:0.5, the mass ratio of PA66, toughening agent, UV absorber and antioxidant was 25:1:0.5:0.4, the mass ratio of PA11, toughening agent, UV absorber and antioxidant was 7:0.5:0.2:0.2, and the mass ratio of bio-based nylon, toughening agent, UV absorber and antioxidant was 5:0.1:0.1:0.1;

[0050] Step S2: high-speed mixing: first, PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer treated in step S1 are added to a high-speed mixer, and stirred at a speed of 900 rpm for 45 minutes at room temperature to form a premix, and then silane coupling agent, nucleating agent, hollow glass microspheres and mica are added to the premix, and the mixing is continued for 10-20 minutes at a heating temperature of 320-350°C. A composite material is obtained, in which the mass ratios of PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microspheres and mica are 40:24:7:5:2:40:2:0.3:1:0.6:0.2:2:4, the particle size range of mica is 100 μm, the diameter of the glass fiber is 5 μm, the length is 1 mm, and the particle size range of the hollow glass microspheres is 10 mm.

[0051] Furthermore, the test results showed that the tensile strength was 275 MPa, the flexural strength was 396 MPa, the heat deformation temperature was 272°C, and the apparent quality score was 8. After corrosion with alcohol aqueous solution, the tensile strength was 267 MPa, the flexural strength was 389 MPa, and the apparent quality score was 7.

[0052] Embodiment 2:

[0053] Step S1: raw material pretreatment: first use a silane coupling agent to perform surface treatment on the glass fiber, then use nanoparticles to modify the surface of the glass fiber, and then use the modified glass fiber for standby use, then dry PA46, PA66, PA11 and bio-based nylon at a temperature of 90°C for 2 hours, then add toughening agents to the dried PA46, PA66, PA11 and bio-based nylon, and mix them with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 850rpm, and the stirring time is 25min, and then add ultraviolet absorbers, The mixture was stirred at 850 rpm for 20 min, and then the antioxidant was added into the high-speed mixer and stirred at 850 rpm for 20 min, wherein the mass ratio of PA46, toughening agent, UV absorber and antioxidant was 40:2:0.7:0.5, the mass ratio of PA66, toughening agent, UV absorber and antioxidant was 25:1:0.5:0.4, the mass ratio of PA11, toughening agent, UV absorber and antioxidant was 7:0.5:0.2:0.2, and the mass ratio of bio-based nylon, toughening agent, UV absorber and antioxidant was 5:0.1:0.1:0.1;

[0054] Step S2: high-speed mixing: first, PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer treated in step S1 are added to a high-speed mixer, and stirred at a speed of 900 rpm for 45 minutes at room temperature to form a premix, and then silane coupling agent, nucleating agent, hollow glass microspheres and mica are added to the premix, and the premix is ​​mixed for 10-20 minutes at a heating temperature of 320-350°C. , a composite material was obtained, in which the mass ratio of PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microspheres and mica was 38:22:6:4:2:38:2:0.3:2:1:0.2:2:4, the particle size range of mica was 100 μm, the diameter of the glass fiber was 5 μm and the length was 1 mm, and the particle size range of the hollow glass microspheres was 10 mm.

[0055] Furthermore, the test results showed that the tensile strength was 289 MPa, the flexural strength was 406 MPa, the heat deformation temperature was 283°C, and the apparent quality score was 9. After corrosion with alcohol aqueous solution, the tensile strength was 284, the flexural strength was 398 MPa, and the apparent quality score was 8.

[0056] Embodiment three:

[0057] Step S1: raw material pretreatment: first use a silane coupling agent to perform surface treatment on the glass fiber, then use nanoparticles to modify the surface of the glass fiber, and then use the modified glass fiber for standby use, then dry PA46, PA66, PA11 and bio-based nylon at a temperature of 90°C, and the drying time is 2 hours, then add toughening agents to the dried PA46, PA66, PA11 and bio-based nylon, and mix them with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 850rpm, and the stirring time is 25min, then add ultraviolet absorber, continue stirring at a speed of 850rpm for 20min, and then add antioxidant to the high-speed mixer and stir at a speed of 850rpm for 20min, wherein the mass ratio of PA46, toughening agent, ultraviolet absorber and antioxidant is 35:

[0058] 2.5:0.7:0.6, the mass ratio of PA66, toughening agent, UV absorber and antioxidant is 24:2:0.5:0.5, the mass ratio of PA11, toughening agent, UV absorber and antioxidant is 6:0.5:0.2:0.2, and the mass ratio of bio-based nylon, toughening agent, UV absorber and antioxidant is 3:0.2:0.1:0.1;

[0059] Step S2: high-speed mixing: first, PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer treated in step S1 are added to a high-speed mixer, and stirred at a speed of 900 rpm for 45 minutes at room temperature to form a premix, and then a silane coupling agent, a nucleating agent, hollow glass microspheres and mica are added to the premix, and the mixture is mixed for 10-20 minutes at a heating temperature of 320-350°C to obtain To a composite material, the mass ratio of PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microspheres and mica is 35:22:6:3:2:26:2:0.2:2:1.5:0.3:2.5:4, the particle size range of mica is 50μm, the diameter of the glass fiber is 5μm, the length is 2mm, and the particle size range of the hollow glass microspheres is 15mm.

[0060] Furthermore, the test tensile strength was 298 MPa, the flexural strength was 424 MPa, the heat deformation temperature was 296°C, and the apparent quality score was 10. After corrosion with alcohol aqueous solution, the tensile strength was 291 MPa, the flexural strength was 411 MPa, and the apparent quality score was 10.

[0061] Embodiment 4:

[0062] Step S1: raw material pretreatment: first use a silane coupling agent to perform surface treatment on the glass fiber, then use nanoparticles to modify the surface of the glass fiber, and then use the modified glass fiber for standby use, then dry PA46, PA66, PA11 and bio-based nylon at a temperature of 90°C, and the drying time is 2 hours, then add toughening agents to the dried PA46, PA66, PA11 and bio-based nylon, and mix them with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 850rpm, and the stirring time is 25min, then add ultraviolet absorber, continue stirring at a speed of 850rpm for 20min, and then add antioxidant to the high-speed mixer and stir at a speed of 850rpm for 20min, wherein the mass ratio of PA46, toughening agent, ultraviolet absorber and antioxidant is 35:

[0063] 2.5:0.7:0.6, the mass ratio of PA66, toughening agent, UV absorber and antioxidant is 24:2:0.5:0.5, the mass ratio of PA11, toughening agent, UV absorber and antioxidant is 6:0.5:0.2:0.2, and the mass ratio of bio-based nylon, toughening agent, UV absorber and antioxidant is 3:0.2:0.1:0.1;

[0064] Step S2: high-speed mixing: first, PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer treated in step S1 are added to a high-speed mixer, and stirred at a speed of 900 rpm for 45 minutes at room temperature to form a premix, and then a silane coupling agent, a nucleating agent, hollow glass microspheres and mica are added to the premix, and the mixture is mixed for 10-20 minutes at a heating temperature of 320-350°C to obtain To a composite material, the mass ratio of PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microspheres and mica is 35:23:6:4:2:21:2:0.3:2:1.5:0.3:2.5:4, the particle size range of mica is 50μm, the diameter of the glass fiber is 5μm, the length is 2mm, and the particle size range of the hollow glass microspheres is 15mm.

[0065] Furthermore, the test results showed that the tensile strength was 293 MPa, the flexural strength was 433 MPa, the heat deformation temperature was 292°C, and the apparent quality score was 10. After corrosion with an alcohol-water solution, the tensile strength was 289 MPa, the flexural strength was 403 MPa, and the apparent quality score was 9.

[0066] Embodiment five:

[0067] Step S1: raw material pretreatment: first use a silane coupling agent to perform surface treatment on the glass fiber, then use nanoparticles to modify the surface of the glass fiber, and then use the modified glass fiber for standby use, then dry PA46, PA66, PA11 and bio-based nylon at a temperature of 90°C, and the drying time is 2 hours, then add toughening agents to the dried PA46, PA66, PA11 and bio-based nylon, and mix them with a high-speed mixer, wherein the stirring speed of the high-speed mixer is 850rpm, and the stirring time is 25min, then add ultraviolet absorber, continue stirring at a speed of 850rpm for 20min, and then add antioxidant to the high-speed mixer and stir at a speed of 850rpm for 20min, wherein the mass ratio of PA46, toughening agent, ultraviolet absorber and antioxidant is 35:

[0068] 2.5:0.7:0.6, the mass ratio of PA66, toughening agent, UV absorber and antioxidant is 24:2:0.5:0.5, the mass ratio of PA11, toughening agent, UV absorber and antioxidant is 6:0.5:0.2:0.2, and the mass ratio of bio-based nylon, toughening agent, UV absorber and antioxidant is 3:0.2:0.1:0.1;

[0069] Step S2: high-speed mixing: first, PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer treated in step S1 are added to a high-speed mixer, and stirred at a speed of 900 rpm for 45 minutes at room temperature to form a premix, and then a silane coupling agent, a nucleating agent, hollow glass microspheres and mica are added to the premix, and the mixture is mixed for 10-20 minutes at a heating temperature of 320-350°C to obtain To a composite material, the mass ratio of PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent, compatibilizer, silane coupling agent, nucleating agent, hollow glass microspheres and mica is 36:23:5:4:2:22:2:0.2:0.2:1:0.2:2:4, the particle size range of mica is 30μm, the diameter of the glass fiber is 5μm, the length is 1.5mm, and the particle size range of the hollow glass microspheres is 15mm.

[0070] Furthermore, the test tensile strength was 285 MPa, the flexural strength was 395 MPa, the heat deformation temperature was 286°C, and the apparent quality score was 9. After corrosion with alcohol aqueous solution, the tensile strength was 276 MPa, the flexural strength was 391 MPa, and the apparent quality score was 8.

[0071] Comparative Example:

[0072] The existing nylon glass fiber material is used as a comparative example, and the tested tensile strength is 256 MPa, the bending strength is 349 MPa, the heat deformation temperature is 251°C, and the apparent quality score is 8. After corrosion by alcohol aqueous solution, the tensile strength is 238 MPa, the bending strength is 315 MPa, and the apparent quality score is 7.

[0073] The results of the physical properties test and environmental resistance test of high alcoholysis resistant glass fiber reinforced nylon material are as follows:

[0074]

[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A highly alcoholysis-resistant glass fiber reinforced nylon material, characterized by: The raw materials include the following components by weight: 30-43 parts of PA46, 20-25 parts of PA66, 7 parts of PA115, 3-5 parts of bio-based nylon, 20-45 parts of alkali-free glass fiber, 1-3 parts of polyethylene, 0.5-3 parts of antioxidant, 0.2-3 parts of heat stabilizer, 0.1-5 parts of compatibilizer, 1-5 parts of toughening agent, 0.2-0.5 parts of hydrolysis resistance agent, 1-2 parts of ultraviolet absorber, 0.1-2 parts of silane coupling agent, 0.1-0.5 parts of nucleating agent, 1-5 parts of hollow glass microspheres, and 3-8 parts of mica; PA46, PA66, PA11, bio-based nylon, glass fiber, polyethylene, antioxidant, heat stabilizer, compatibilizer, toughening agent, hydrolysis resistance agent, UV absorber, silane coupling agent, nucleating agent, hollow glass microspheres and mica are mixed to prepare glass fiber reinforced nylon material, which has better alcoholysis resistance than conventional nylon material.

2. The high alcoholysis-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The mica is one or more of muscovite, phlogopite, biotite, lepidolite and sericite, and its particle size range is 1-200 μm.

3. The high alcoholysis-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber has a diameter of 5-7 μm and a length of 1-2 mm.

4. The high alcoholysis-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The particle size of the hollow glass microspheres ranges from 10 to 20 mm.

5. The high alcoholysis-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The nucleating agent is one of an inorganic nucleating agent, an organic nucleating agent and a polymer nucleating agent.

6. A method for preparing a highly alcoholysis-resistant glass fiber reinforced nylon material, applicable to the highly alcoholysis-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The preparation method of the high alcoholysis-resistant glass fiber reinforced nylon material is as follows: Step S1: raw material pretreatment: modifying the alkali-free glass fiber to obtain modified glass fiber, and drying, toughening modification and weathering modification of PA46, PA66, PA11 and bio-based nylon respectively; Step S2: high-speed mixing: adding the modified glass fiber in step S1, the pretreated PA46, PA66, PA11 and bio-based nylon, polyethylene, heat stabilizer, compatibilizer, hydrolysis resistance agent, silane coupling agent, nucleating agent, hollow glass microspheres and mica to a high-speed stirring agent in sequence and mixing to obtain a composite material; Step S3: extrusion molding: extruding the mixed composite material through a twin-screw extruder to obtain the final alcoholysis-resistant glass fiber reinforced nylon material; Step S4: post-treatment: placing the alcoholysis-resistant glass fiber reinforced nylon material obtained in step S3 into hot water at a constant temperature of 80-90° C., keeping the temperature for 40-50 minutes, and performing drying treatment; Step S5: Performance test: Perform a comprehensive quality test on the alcoholysis-resistant glass fiber reinforced nylon material treated in step S4.

7. The method for preparing a highly alcoholysis-resistant glass fiber reinforced nylon material according to claim 6, characterized in that: The step S1 further includes the following steps: Step S11: Modifying glass fiber: firstly using a silane coupling agent to perform surface treatment on the glass fiber, and then using nanoparticles to modify the surface of the glass fiber; Step S12: Drying treatment: First, PA46, PA66, PA11 and bio-based nylon are dried respectively, wherein the drying temperature is 90-100° C. and the drying time is 2 hours; Step S13: toughening modification: then, toughening agents are added to the dried PA46, PA66, PA11 and bio-based nylon respectively, and mixed by a high-speed mixer, wherein the stirring speed of the high-speed mixer is 800-900 rpm, and the stirring time is 20-30 min; Step S14: Weathering resistance modification: Then add the ultraviolet absorber to the materials stirred in step S13, continue stirring at a speed of 800-900 rpm for 20-30 minutes, and then add the antioxidant to the high-speed mixer and stir at a speed of 800-900 rpm for 20 minutes.

8. The method for preparing a highly alcoholysis-resistant glass fiber reinforced nylon material according to claim 6, characterized in that: The step S2 further includes the following steps: Step S21: Preliminary mixing: first add PA46, PA66, PA11, bio-based nylon, polyethylene, modified glass fiber, heat stabilizer, hydrolysis resistance agent and compatibilizer into a high-speed mixer, and stir at a speed of 900-1000 rpm for 30-45 minutes at room temperature to form a premix; Step S22: high temperature mixing: then add silane coupling agent, nucleating agent, hollow glass microspheres and mica to the premix, and continue mixing for 10-20 minutes at a heating temperature of 320-350° C. to obtain a composite material.

9. The method for preparing a highly alcoholysis-resistant glass fiber reinforced nylon material according to claim 6, characterized in that: The step S3 further includes the following steps: Step S31: extrusion granulation: the mixed composite material is added into a twin-screw extruder from a main feed port, and extrusion granulation is performed under the conditions of an extrusion temperature of 255-260° C. and a rotation speed of 850 rpm; Step S32: Cooling and pelletizing: firstly cool the material extruded in step S31 with water, and then pelletize it with a special pelletizer to obtain the final alcoholysis-resistant glass fiber reinforced nylon material.

10. The method for preparing a highly alcoholysis-resistant glass fiber reinforced nylon material according to claim 6, characterized in that: The step S5 further includes the following steps: Step S51: Physical property test: the prepared alcoholysis-resistant glass fiber reinforced nylon material is placed in a drying oven at 120°C for 5 hours, and then the dried material is injected into a sample by an injection molding machine, and the mold temperature is 70°C. Then, the tensile strength is tested according to the ISO527-2 method, the bending strength is tested according to the ISO178 method, and the heat deformation temperature is tested according to the national standard GB / T1634.

1. At the same time, the material is visually evaluated for its apparent quality. The score of the custom apparent quality is 0-10, where 10 points means that the material surface is smooth and has no floating fibers, and 0 points means that 80% to 100% of the surface area of ​​the material has floating fibers; Step S52: Environmental resistance test: A hydrolysis and alcoholysis resistance test was performed according to Volkswagen TL52682 standard. The sample was placed in a mixed solution at 100° C. and a volume ratio of ethylene glycol to aqueous solution of 1:1 for 7 days, and then its tensile strength and bending strength were tested and the apparent quality of the sample was observed.

Citation Information

Patent Citations

  • Nylon glass fiber reinforced alcohol-resistant material

    CN107236296B

  • A hydrolysis- and alcoholysis-resistant reinforced nylon material and its preparation method

    CN107298855B

  • A high glass fiber reinforced nylon composite material, its preparation method and application

    CN111662546B

  • Hydrolysis-resistant alcoholysis-resistant reinforced nylon material and preparation method thereof

    CN115710429A

Cited By

  • Halogen corrosion resistant composite material and preparation method thereof

    CN120248607A

  • Halogen corrosion-resistant composite material and preparation method thereof

    CN120248607B